Development of multi-type interior permanent magnet motor - Abdullah, Ami Nurul Nazifah (2011)
A new three-phase Multi-type Interior Permanent Magnet Motor (MT-IPM) is proposed in this research. The type of motor is designed for high torque performance with diameter of 200mm and thickness of 30mm. The main advantage of this motor is to act as two types of motor as a Permanent Magnet Stepper Motor (PMST) and as a Permanent Magnet Brushless DC Motor (BLDC). BLDC operates in bi-directional variable speed operation in full torque mode. In BLDC, the speed is simply controlled by DC supply voltage. However the BLDC motor requires essentially an input feedback from rotor position sensor unlike PMST that controls commutation sequences by using a frequency controller technique. PMST is usually run at high torque at low speed. Unfortunately, PMST is suitable only for large step angles applications as it is stepped by pulse frequency technique. Also missing or over stepping in the sequence of commutation occurs during the rotor rotation in a PMST for smaller step angles.With this aim, the development of a three-phase multifunctional motor that act as brushless and stepper motor is proposed. This research also proposes new pitch arrangement of three-phase motor. The coils were arranged in a group according to their respective phases. Analyzing torque characteristic and motor performance of MT-IPM on various sizes of magnet and rotor are essential. The optimum model is derived and fabricated for various experimental testing to validate the performance of the proposed motor. At the early stage, simulation analysis using finite element method (FEM) is performed to analyze the magnetic circuit on various sizes of rotor and magnet. The analysis parameters include the magnetic field flux, the cogging force and the developed torque. Further study on the research is then done to analyze the performance of the MT-IPM by using related mathematical model. The parameters considered are no load speed, no load current, stall torque and efficiency of the motor. Heat increment in coil is also taken into account during the observations. Overall analyses are done based on volume of magnet. Thus, the MT-IPM proposed is based on optimum result for testing in a laboratory environment. As the result, optimized model are identified for the motors with volume of magnet between 2000mm3 to 4000mm3. The permanent magnet volume chosen for this MT-IPM is 3600mm3 with the selected size of rotor as 50mm. Based on the measurement results, the optimum output torque with low cogging force of 6.5 Nm is achieved at phase current of 5A. Also the coil current when run as PMST motor is higher than BLDC motor.